T-cell-mediated cytotoxicity against autologous malignant melanoma: analysis with interleukin 2-dependent T-cell cultures. - Knuth, A (1984)
The cytotoxic reactivity of lymphocytes for autologous melanoma cells was studied in a group of 13 melanoma patients. No cytotoxicity was observed with lymphocytes freshly isolated from peripheral blood or with lymphocytes cocultured for 7 days with autologous melanoma cells. Growth of lymphocytes previously sensitized with autologous melanoma in vitro in interleukin 2 (IL-2)-containing medium, however, resulted in cytotoxic reactivity for autologous melanoma in 7/13 patients. The reactivity of IL-2-dependent lymphocytes for autologous melanoma was particularly striking in one patient (A.V.) who has had an unexpectedly favorable clinical course and, because of their consistently high reactivity, AV lymphocytes were selected for detailed specificity analysis. After 2-3 weeks in culture in IL-2-containing medium, AV lymphocytes were cytolytic for autologous melanoma cells but not autologous Epstein-Barr virus-transformed B cells, autologous fibroblasts, or allogeneic tumor targets. Specificity of autologous melanoma reactivity was confirmed by competitive inhibition assays. The IL-2-dependent AV lymphocytes formed rosettes with sheep erythrocytes and expressed OKT 3 and Ia antigens. After longer periods of culture, AV lymphocytes were found to react with a wider range of target cells, and repeated attempts to isolate cultures with restricted reactivity to autologous melanoma by resensitization with autologous melanoma and limiting-dilution techniques were unsuccessful. The restricted reactivity of early cultures could be preserved, however, in frozen storage, but shifted again toward broader reactivity after several weeks in culture. The recognition of cytotoxic T cells with initial restricted reactivity for autologous melanoma suggests reinvestigation of the question of specific cellular immunity to human cancer.